(untitled) (Bangladesh Pharmaceutical Journal, 2019)
Wedelia chinensis is a widely used anti-inflammatory and hepatoprotective medicinal plant in Bangladesh. In this study, analgesic, neurological, antioxidant and cytotoxic activities of the ethanolic extract of leaf and stem bark of W. chinensis were investigated. Oral administration of the ethanolic extract of W. chinensis (200- and 300-mg/kg body weight) was investigated on animal model for neurological activity using open field test and hole cross test. Acetic acid induced writhing method was used to assess the analgesic activity. DPPH (1,1-diphenyl, 2-picryl hydrazyl) radical scavenging assay was used for determining the antioxidant activity, while brine shrimp lethality bioassay was used for investigating cytotoxicity. The ethanol extract of the plant produced significant reduction (P<0.05) of locomotion in both doses (200- and 300-mg/kg body weight) indicating pronounced neurological activity. Oral administration of alcoholic leaves and stem extracts significantly (p < 0.05) inhibited writhing response in mice. The percentage of scavenging of DPPH free radical was found to be concentration dependent with IC50 value of 44.10 ± 0.65 and 38.96 ± 0.50 μg/ml for leaves and stem extracts, respectively. Our findings indicate that W. chinensis may be a source of natural antioxidant with potent analgesic, neurological and cytotoxic activities. Bangladesh Pharmaceutical Journal 22(1): 18-26, 2019